Fever of unknown origin following parathyroidectomy prior to onset of typical polymyalgia rheumatica symptoms: a case report - Kanzaki A; Matsui K; Sukenaga T; Mase K; Nishioka A; Tamori T; Kataoka S; Konya H; Mizutani S; Takeda A; Koseki M; Nishiura T; et al. (International Journal of General Medicine, 2018)
Akinori Kanzaki,1,2 Kiyoshi Matsui,3 Tadahiko Sukenaga,1,2 Koushi Mase,1 Aya Nishioka,1 Tomoharu Tamori,4 Seiko Kataoka,1 Hiroyuki Konya,1 Shin Mizutani,4 Akira Takeda,1 Masato Koseki,1 Tetsuo Nishiura,1 Hidenori Koyama,2 Hajime Sano3 1Department of Internal Medicine, Ashiya Municipal Hospital, Ashiya, Hyogo, Japan; 2Division of Diabetes, Endocrinology and Metabolism, Department of Internal Medicine, Hyogo College of Medicine, Nishinomiya, Hyogo, Japan; 3Division of Rheumatology, Department of Internal Medicine, Hyogo College of Medicine, Nishinomiya, Hyogo, Japan; 4Department of Surgery, Ashiya Municipal Hospital, Ashiya, Hyogo, Japan Abstract: Polymyalgia rheumatica (PMR) is a disease commonly seen in elderly individuals, however, the etiology has not been reported. Typical clinical features include bilateral shoulder pain and morning stiffness, while serologic autoantibody test findings are negative. Approximately 40%–50% of affected patients present with low-grade fever, fatigue, and appetite loss, which we often experience in the field of general medicine, and thus, the condition should not be given low priority. However, knowledge regarding such constitutional manifestations is also limited. We encountered an elderly woman with a fever of unknown origin that developed following a parathyroidectomy for a single parathyroid adenoma, after which severe shoulder pain and morning stiffness emerged, leading to a diagnosis of PMR. The fever developed several days prior to appearance of severe pain, which is an uncommon presentation in PMR cases. Our patient had low-grade inflammation without pyrexia prior to the surgery, which might have been an important reason for the accelerated immoderate immune activation leading to PMR induced by surgery in this case. Furthermore, she was infected with the influenza A virus 3 weeks before coming to us. Some reports have suggested a relationship between the influenza virus or vaccine and PMR. It is difficult to conclude regarding the definite trigger in our patient, though the details of this case should be helpful for a better understanding of the disease. Keywords: polymyalgia rheumatica, fever of unknown origin, immoderate immune activation, parathyroidectomy, influenza A viral infection, single parathyroid adenoma